2018
DOI: 10.18844/gjs.v8i1.3411
|View full text |Cite
|
Sign up to set email alerts
|

Changing dynamics of early marriage in rural areas of northern Nigeria

Abstract: The paper examines the changes that occurred over time between Christians and Muslim in rural settlements. The study collected data from focus group discussions (FGDs) with married literate adolescent girls and unmarried non-literate adolescent girls. Christian and Muslim faith leaders as well as a government official were interviewed. The study revealed the rising rate of early marriage among Christians who were hitherto known to the delayed marriage of girl-child above 18 years. These changes have been attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another possible reason for this finding could be early marriage (less than 18 years) among adolescents, which reduces their autonomy to negotiate for safer sex, increasing their likelihood of getting pregnant in their adolescence stage [ 30 ]. Maigari [ 31 ] examined the changing rates of early marriages in northern Nigeria and found that these changing dynamics of early marriages were as a result of increased rates of poverty in Nigeria, with over 39% of Nigeria living below the international poverty line of $1.90 per day [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason for this finding could be early marriage (less than 18 years) among adolescents, which reduces their autonomy to negotiate for safer sex, increasing their likelihood of getting pregnant in their adolescence stage [ 30 ]. Maigari [ 31 ] examined the changing rates of early marriages in northern Nigeria and found that these changing dynamics of early marriages were as a result of increased rates of poverty in Nigeria, with over 39% of Nigeria living below the international poverty line of $1.90 per day [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason could be the pressure given to female adolescents to marry early and a subsequent expectation of getting pregnant [ 44 ]. For instance, a qualitative study conducted in northern Nigeria by Maigari [ 31 ] revealed that the parents of teenagers believed that when teenage girls are left unmarried, they may bring shame to the family after getting pregnant out of wedlock which is seen as a taboo; hence they are pushed into marriage early. As a way of addressing the problem of early marriage in Nigeria, the Federal Government in 2003 passed the Child Rights Act that criminalizes marriage below age 18, yet some states are yet to institute the policy as at 2020 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Society and family are always in good or bad interaction. The place and value of the family in the society is determined by the responsibilities it undertakes and the functions it fulfills (Maigari, 2018;Ergin, 2012).…”
Section: Introductionmentioning
confidence: 99%